SNARE Protein Syntaxin-1 Colocalizes Closely with NMDA Receptor Subunit NR2B in Postsynaptic Spines in the Hippocampus - Hussain, Suleman; Ringsevjen, Håvard; Egbenya, Daniel L.; Skjervold, Torstein L.; Davanger, Svend (Frontiers in Molecular Neuroscience, 2016)
Syntaxins are a family of membrane-integrated proteins that are instrumental in exocytosis of vesicles. Syntaxin-1 is an essential component of the presynaptic exocytotic fusion machinery in the brain and interacts with several other proteins. Syntaxin-1 forms a four-helical bundle complex with proteins SNAP-25 and VAMP2 that drives fusion of vesicles with the plasma membrane in the active zone. Little is known, however, about the ultrastructural localization of syntaxin-1 at the synapse. We have analysed the intrasynaptic expression of syntaxin-1 in glutamatergic hippocampal synapses in detail by using quantitative postembedding immunogold labeling. Syntaxin-1 was present in highest concentrations at the presynaptic active zone, supporting its role in transmitter release. Presynaptic plasma membrane lateral to the active zone, as well as presynaptic cytoplasmic vesicles were also labeled. However, syntaxin-1 was also significantly expressed in postsynaptic spines, where it was localized at the postsynaptic density, at postsynaptic lateral membranes and in postsynaptic cytoplasm. Postsynaptically, syntaxin-1 colocalized in the nanometer range with the NMDA receptor subunit NR2B, but only weakly with the AMPA receptor subunits GluA2/3. This observation points to the possibility that syntaxin-1 may be involved with NR2B vesicular trafficking from cytoplasmic stores to the postsynaptic plasma membrane, thus facilitating synaptic plasticity. Confocal immunofluorescence double labeling with PSD-95 and ultrastructural fractionation of synaptosomes also confirm localization of syntaxin-1 at the postsynaptic density.